2020
DOI: 10.1155/2020/8824783
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Mechanical Stimulations in Tendon Tissue Engineering

Abstract: Tendon injury is the most common disease in the musculoskeletal system. The current treatment methods have many limitations, such as poor therapeutic effects, functional loss of donor site, and immune rejection. Tendon tissue engineering provides a new treatment strategy for tendon repair and regeneration. In this review, we made a retrospective analysis of applying mechanical stimulation in tendon tissue engineering, and its potential as a direction of development for future clinical treatment strategies. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 88 publications
0
33
0
Order By: Relevance
“…Although stem cells derived from bone marrow (BMSCs), adipose tissue (ASCs) and tendon/ligament tissues (TDSCs) have shown their efficacy as seed cells in tendon tissue engineering [27 , 28] , PDLSCs could be another good choice in spite that their potential in promoting tendon repair and regeneration should be further explored. To be a seed cell for tissue engineering application, the first important concern is accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…Although stem cells derived from bone marrow (BMSCs), adipose tissue (ASCs) and tendon/ligament tissues (TDSCs) have shown their efficacy as seed cells in tendon tissue engineering [27 , 28] , PDLSCs could be another good choice in spite that their potential in promoting tendon repair and regeneration should be further explored. To be a seed cell for tissue engineering application, the first important concern is accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…Physical signals are equally a focus of research as moderate mechanical stimulation ensures maintenance of the natural phenotype of tissues [10]. Mechanical stimulation methods are therefore used to generate a specific tissue phenotype in TERM such as cartilage [11], tendon [12], or cardiac muscle tissue [13].…”
Section: Tissue Engineering and Regenerative Medicine (Term) 21 Fundamentals Of Tissue Engineering And Regenerative Medicinementioning
confidence: 99%
“…In terms of strain a wide variety of stimulus regimes have been used, with a consensus that uniaxial strain is more beneficial than biaxial strain for myogenesis at strain amplitudes of 10-15% [95]. Additionally, mechanical loading should be applied on cells in a 3D environment as studies have shown that this mimics mechanical loading in natural systems [96]. Under appropriate conditions the 3D loading of cells allows them to recognize mechanical stimulation as cell-ECM interactions, which results in the precise differentiation desired in the reconstruction of native muscle [97].…”
Section: External Stimuli For Muscle Cell Differentiationmentioning
confidence: 99%